Revision of Polypedilum (Pentapedilum) Kieffer and Ainuyusurika Sasa et Shirasaki (Diptera: Chironomidae) - Oyewo, Emmanuel Adeoye; Sæther, Ole A. (Zootaxa, 2008)
Six new species are described as males: P. (Pe.) botiense, P. (Pe.) botosaneanui, P. (Pe.) camposense, P. (Pe.) intuber, P. (Pe.) reei, and P. (Pe.) tissamaharense. One additional species is described as female imago. P. (Pe.) pseudotritum and P. (Pe.) utonaiprimum are synonyms of P. (Pe.) tigrinum, and P. (Pe.) takorageheum and P. (Pe.) famibeceum synonyms of P. (Pe.) furusecundum. Five species misidentified as Pentapedilum and one as Polypedilum s. str. have been transferred, four to Polypedilum s. str. [P. (P.) inaijeum Sasa, Kitami et Suzuki, P. (P.) iriodeeum Sasa et Suzuki, P. (P.) jokasecundum Sasa et Ogata, and P. (P.) parasordens Ree], one to Ainuyusurika [A. yakuabeum (Sasa et Suzuki)] and one to P. (Uresi- pedilum). P. (Pe.) pseudotritum and P. (Pe.) utonaiprimum are synonymized with P. (Pe.) tigrinum, and P. (Pe.) tokarageheum and P. (Pe.) famibeceum synonymized with P. (Pe.) furudosecundum. Subgeneric diagnoses are given for all stages and sexes of the subgenus Pentapedilum Kieffer. Keys are provided for all stages and sexes of all available material from all zoogeographical regions. The phylogenetic analysis, which included some species of Polypedilum s. str. and all available Pentapedilum indicate that Pentapedilum is likely monophyletic, while Polypedilum s. str. is polyphyletic. The subgenus Pentapedilum can be divided into three relatively distinct apical groups and the remaining species in a basal Hennigian comb when a parsimony analysis is done. The convexum group consists of one Afrotropical species, and five High, East and South Asian species with one of them also occurring in the Indo-Pacific. The sordens group consists of 13 species from Asia, the Indo-Pacific and Africa. The apparently paraphyletic uncinatum group consists of 9 species from the Holarctic and Oriental regions. The zoogeographical distribution does not support any vicariance patterns, but indicates that the present distribution is caused by dispersal. Diagnostic characters and keys to the males of Ainuyusurika Sasa et Shirasaki is given and Pentapedilum yakuabeum Sasa et Suzuki and Polypedilum (P.) yakucedeum Sasa et Suzuki assigned to the genus. The genus appears to be close to Phaenopsectra Kieffer and is known from Japan only.